Pengembangan Sistem Informasi Geografis Pemetaan Tower Base Transceiver (BTS) Berbasis Web Menggunakan Metode Waterfall - Muhammad Rivaldi; Khairul Abdi; Imam Adlin Sinaga (Bulletin of Computer Science Research, 2024)
Tower Base Transfer Receiver or BTS plays an important role in providing more stable internet services to users. BTS Tower is used as the main access point so that devices can connect to each other and communicate between the same network. Medan Communication and Information Agency as the agency responsible for government affairs in the field of technology and informatics plays an important role in ensuring that BTS Tower operations can run smoothly. One of its tasks is to carry out monitoring, evaluation and reporting activities on information technology infrastructure such as BTS Tower. In carrying out its operational activities, Medan Communication and Information Agency stores data related to BTS Tower in the form of physical documents and digital files such as Microsoft Word & Excel. This will later cause the process of retrieving data related to BTS Tower to be slower because data related to BTS Tower is stored separately. In addition, technicians are often confused because of the large number of BTS Towers spread across various locations. The process of identifying and navigating to the Tower location often takes a long time which causes the maintenance process to be hampered. Therefore, a system was created that can be used as integrated storage that facilitates the process of archiving BTS Tower operational documents. The system that was built also provides a digital map that presents information about the distribution location of BTS Towers that are under the supervision of Medan Communication and Information Agency. The digital map can be used by field technicians for the identification and navigation process to the BTS Tower location, making it easier to maintain the BTS Tower. The system development in this study uses the Software Development Life Cycle Waterfall model. The system is built using the CodeIgniter Framework with the PHP programming language and the MySql database. The creation of digital maps uses the help of Leaflet Library javascript, Google Maps API and also Open StreatMap. The results of this study are Web-Gis which can facilitate the process of archiving documents and viewing data on the distribution of BTS Tower locations under the supervision of the Medan Kominfo service. The test results using the Black-Box testing method show that the features and functions of the system can run properly.